Fixtures design for thin-walled cylindrical workpieces on the principles of group technology - Vukelić, Đorđe; Sokac, Mario; Budak, Igor; Matin, Ivan; Santosi, Zeljko (Journal of Production Engineering, 2019)
This paper presents the methodology for fixture design based on the principles of group technology. The combination of the geometry-based and knowledge-based methods was used to develop a system for fixture design. The presented case study shows the implementation of the methodology for the inspection operations of the characteristic dimensions of the aluminium caps on a coordinate measuring machine.